Gas Permeable-Membrane for Hydrogenotrophic Denitrification - Hasar, Halil; Ipek, Ubeyde (Wiley-V C H Verlag Gmbh, 2010)
The membrane biofilm reactor (MBfR) involves a process in which the membrane provides effective H(2) Utilization as an electron donor. MBfRs overcome the problems caused from the particularly low solubility of the gas delivered into a liquid by means of a gas-permeable membrane. The study demonstrates that the MBfR is successful in the effective removal of nitrate from drinking water or nitrified water, involving a hydraulic retention time of 25 min for a maximum nitrate removal of 98%. The H(2) flux reaches a level of 1.24 g H(2)/m(2) d when the denitrification rate achieves 3.5 g N/m(2) d at 0.2 atm H(2) pressure. The results indicate that the biofilm on outer walls of the gas permeable membrane utilizes all of the H(2) gas effectively as an electron donor since the H(2) is not detectable in the bulk liquid. In the future, the MBfR could be an attractive process for water and wastewater engineers due to its applicability for treatment of secondary effluent from industrial and municipal wastewater and drinking water.
Keywords: Denitrification rate; Hydrogen flux; Hydrogenotrophic denitrification; Membrane biofilm reactor; Nitrate flux